English Training and Entrepreneurship dalam Mendukung Wisata Budaya di Karampuang - Jusniaty; Baharuddin; Sri Rahayu Juniati; Hasdinawati; Syamsiah Hasyim; Supratman Tahir (Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LPPM) AMIK Indonesia, 2023)
Community empowerment is one of the supports in developing potential sources of local original income (PAD). For this reason, it is necessary to strengthen the human resources that support the occurrence of PAD. Her one element of the existing talent is youth. One of the efforts to develop this potential is the 'English Training' English Training and Entrepreneurship Management Office for Young People of Kalampuan Hamlet, Tompobul Village. The types of activities of this program and the technical implementation of the activities are: (1) Pree Test (a test that the tutor conducts before giving the material to the target), (2) Giving Material (the tutor provides the material to the target), (3) Post Test (a test given to the target) Partner) target partner becomes available). (Performed at the end of the training to know the degree of change before and after the training), (4) Brainstorming (brainstorming of entrepreneurial ideas). As a result of the activity, we obtained data that English learning was beneficial for the target group from the change in data values ​​before and after the test. On the other hand, regarding the business types of the target group, it was found that the majority of the communities are engaged in palm sugar business, cattle trading business, and broiler business. However, the trade still operates separately and no joint ventures with an organizational structure have been formed, so the processing of official permits (business licenses and labels) cannot be carried out.